2001
DOI: 10.1128/aac.45.3.870-877.2001
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-Binding Proteins in Leptospira interrogans

Abstract: The Leptospira interrogans ponA and pbpB genes were isolated and characterized. ponA and pbpB encode the penicillin-binding proteins (PBPs) 1 and 3, respectively. There is little sequence variation between the PBP genes from two L. interrogans strains (serovar icterohaemorrhagiae strain Verdun and serovar pomona strain RZ11). The deduced L. interrogans PBP 1 and PBP 3 protein sequences from the two strains shared over 50% similarity to homologous proteins from Escherichia coli. It was demonstrated for strain V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Previous studies have shown that Triton X-114 solubilizes the outer membrane of L. kirschneri, leaving behind the protoplasmic cylinder consisting of the cytoplasm surrounded by the inner membrane (27,56). As expected, these studies localized the penicillin-binding proteins to the protoplasmic cylinder of Leptospira (10,27). Furthermore, when the temperature of the solubilized material is raised above the clouding point of the detergent to 37°C, LPS and outer membrane proteins LipL32, LipL36, LipL41, and OmpL1 partition into the detergent phase and periplasmic proteins partition into the aqueous phase (24,25,45).…”
Section: Vol 70 2002supporting
confidence: 58%
“…Previous studies have shown that Triton X-114 solubilizes the outer membrane of L. kirschneri, leaving behind the protoplasmic cylinder consisting of the cytoplasm surrounded by the inner membrane (27,56). As expected, these studies localized the penicillin-binding proteins to the protoplasmic cylinder of Leptospira (10,27). Furthermore, when the temperature of the solubilized material is raised above the clouding point of the detergent to 37°C, LPS and outer membrane proteins LipL32, LipL36, LipL41, and OmpL1 partition into the detergent phase and periplasmic proteins partition into the aqueous phase (24,25,45).…”
Section: Vol 70 2002supporting
confidence: 58%
“…The mechanism of the synergistic effect is still unknown. But the role of penicillin is inhibition of peptidoglycan formation by binding to transpeptidases [42,43]. For γ-mangostin, it may work synergy with penicillin G in breakdown of bacterial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Other PC components that could potentially contaminate the leptospiral OM fractions are the endoflagella, and we have included immunoblots probed with antibody specific for endoflagellar sheath protein (40). Probing of immunoblots with antisera to these proteins is a more rapid and sensitive approach to detection of the PC than the use of radiolabeled or digoxigenin-labeled penicillin binding proteins (6,20).…”
Section: Discussionmentioning
confidence: 99%